Baptism and Church Growth in the Church of Norway - Werner G. Jeanrond (Scandinavian University Press/Universitetsforlaget, 2021)
This article discusses the results of a research project on the relationship between statistically significant church growth in four selected Church of Norway parishes and the practice of baptism in their Sunday service. While the frequency of baptisms may have increased overall attendance at Sunday worship, parishioners at times regret the impact of Sunday service baptism on the ordinary life and development of the congregation. Through the theological eyes of a newcomer to the Church of Norway, this article problematizes the concept of church growth and explores the theological tension between baptism and Eucharist in the life of the church. The overall argument is that it makes little sense to celebrate the sacrament of baptism while not being prepared to engage in a life-long journey with God and fellow disciples of Jesus Christ. Separate and public baptismal services in the church will make it possible to concentrate more fully on the sacramental nature, performance and vocational challenge of baptism – not only for the person being baptised, but for the parish as a whole.